Parental acceptance-rejection in the cypriot family. A social-psychological research on the part/parq - Demetriou, Loucia; Christodoulides, Paul (My University, 2006)
Cross-cultural evidence shows that all children experience more or less acceptance and rejection at the hands of the people most important to them, usually their parents. Research reported here is based on Rohner’s Parental Acceptance- Rejection Theory (PART) [6] of Socialization and conducted using the child version of the Parental Acceptance-Rejection Questionnaire (PARQ) in a sample of 220 Greek speaking Cypriot boys and girls ranging in age from 9-12 years. Our research aimed at (a) developing a profile of the dimension “parental warmth” (acceptancerejection) as experienced by Greek Cypriot children, and (b) drawing cross-cultural comparisons between the Greek Cypriot children’s assessment of parental attitudes and those of their peers in the USA. A two-sample t-test was used to compare the responses of our subjects on the four scales of the instrument regarding gender and nationality.
Keywords: Parental Acceptance-Rejection; Models of Parenting; Socialization